2023
DOI: 10.1001/jamanetworkopen.2023.20222
|View full text |Cite
|
Sign up to set email alerts
|

Association of Statin Use With Risk of Liver Disease, Hepatocellular Carcinoma, and Liver-Related Mortality

Abstract: ImportanceGiven the burden of chronic liver disease on the health care system, more information on the hepatoprotective association of statins in the general population is needed.ObjectiveTo examine whether regular statin use is associated with a reduction in liver disease, particularly hepatocellular carcinoma (HCC) and liver-related deaths, in the general population.Design, Setting, and ParticipantsThis cohort study used data from the UK Biobank (UKB) (individuals aged 37-73 years) collected from baseline (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Dyslipidemia was inversely associated with the risk of HCC in veterans irrespective of cirrhosis and after adjusting for confounders. Although we did not assess the association of statin use, we hypothesize that the inverse association between dyslipidemia and incident HCC is driven by statins because they have been reported to decrease HCC incidence and improve overall survival in patients with cirrhosis . Early exposure to alcohol and tobacco use were also important risks for HCC development, especially in veterans with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia was inversely associated with the risk of HCC in veterans irrespective of cirrhosis and after adjusting for confounders. Although we did not assess the association of statin use, we hypothesize that the inverse association between dyslipidemia and incident HCC is driven by statins because they have been reported to decrease HCC incidence and improve overall survival in patients with cirrhosis . Early exposure to alcohol and tobacco use were also important risks for HCC development, especially in veterans with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who regularly take statins have a 42% reduction in risk of HCC (HR=0.58, 95% CI 0.35-0.96), while new initiation reduces HCC risk by 74% (HR=0.26, 95% CI 0.22=0.31). 181 In patients with alcohol-associated cirrhosis, a nationwide emulated trial established a 33%…”
Section: Statin and Hepatocellular Carcinomamentioning
confidence: 99%
“…233,234 . Recent data support that the risk allele may affect statin responses, including 181,235 . These exciting new data provide groundwork for further exploration of genomic medicine in chemoprevention in CLD and substantiate the need for more studies in diverse populations including investigating sex-based differences.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Nationwide studies revealed statin use’s correlation with reduced HCC development, regardless of DM or LC presence[ 139 ]. Statin therapy is notably advantageous for males, individuals with DM, and those with high fibrosis-4 index at study initiation[ 140 ]. In patients with DM, statin use is linked to a reduced likelihood of advanced fibrosis[ 141 ].…”
Section: Treatmentmentioning
confidence: 99%